Multicultural Education as a Strategy for Promoting Tolerance in Secondary School Settings - Ginna Novarianti Dwi Putri Pramesti; Akhmad Syafi'i; Shobichah Shobichah (Sahabat Publikasi, 2026)
This study aims to analyze the role of multicultural education as a strategic approach to promoting tolerance in secondary school settings. The research employs a qualitative method with a descriptive-exploratory design, involving students, teachers, and school management as key informants. Data were collected through in-depth interviews, observations, and questionnaires to capture both perceptions and real practices of multicultural education. The findings indicate that multicultural education has been partially integrated into the curriculum and school activities, contributing positively to the development of tolerant attitudes and inclusive social interactions among students. However, the implementation remains uneven due to limitations in teachers' competencies, lack of structured training, and variations in students' understanding of diversity values. The study also reveals a gap between conceptual knowledge of tolerance and its consistent application in daily interactions. Despite these challenges, multicultural education demonstrates strong potential as an effective tool for fostering social cohesion in diverse school environments. The study highlights the importance of strengthening institutional support, enhancing teacher capacity, and promoting inclusive school cultures to ensure the sustainability of tolerance-based education. This research contributes to the existing literature by emphasizing the integration of educational and managerial perspectives in multicultural education practices.